Interferon regulatory factor 1 regulates PANoptosis to prevent colorectal cancer - Karki, Rajendra; Sharma, Bhesh Raj; Lee, Ein; Banoth, Balaji; Malireddi, R.K. Subbarao; Samir, Parimal; Tuladhar, Shraddha; Mummareddy, Harisankeerth; Burton, Amanda R.; Vogel, Peter; Kanneganti, Thirumala-Devi (JCI insight, 2020)
Interferon regulatory factor 1 (IRF1) regulates diverse biological functions, including modulation of cellular responses involved in tumorigenesis. Genetic mutations and altered IRF1 function are associated with several cancers. Although the function of IRF1 in the immunobiology of cancer is emerging, IRF1-specific mechanisms regulating tumorigenesis and tissue homeostasis in vivo are not clear. Here, we found that mice lacking IRF1 were hypersusceptible to colorectal tumorigenesis. IRF1 functions in both the myeloid and epithelial compartments to confer protection against AOM/DSS-induced colorectal tumorigenesis. We further found that IRF1 also prevents tumorigenesis in a spontaneous mouse model of colorectal cancer. The attenuated cell death in the colons of Irf1-/- mice was due to defective pyroptosis, apoptosis, and necroptosis (PANoptosis). IRF1 does not regulate inflammation and the inflammasome in the colon. Overall, our study identified IRF1 as an upstream regulator of PANoptosis to induce cell death during colitis-associated tumorigenesis.